Corticotomía: mayor rapidez en el tratamiento ortodóntico - Saavedra Vargas, Jennifer (2018)
The aim of the review is to contribute to the optimization of decision-making based on scientific evidence that explains how the corticotomy contributes to the acceleration of dental movement and whether the advantages are greater than the surgical risks associated with the technique. Corticotomy is defined as the surgical intervention limited to the cortical portion of the alveolar bone. Therefore, unlike an osteotomy, the corticotomy procedure only penetrates the medullary bone, either buccally or lingually. But it is an invasive method in which the patient needs to be correctly selected and informed of the post-operative conditions and the potential risks of surgery. Because it stimulates the process of bone regeneration through controlled surgical injuries, which leads to accelerate tooth movement in orthodontic treatment; with less prolonged activations. It can reduce the time of orthodontic treatment from a third to a quarter of the time typically required. Accelerating tooth movement during the first 2 months after the intervention and long-term effects indicate stability.